2009
DOI: 10.1007/978-3-642-00477-3_7
|View full text |Cite
|
Sign up to set email alerts
|

Needle-Free Vaccine Injection

Abstract: Millions of people die each year from infectious disease, with a main stumbling block being our limited ability to deliver vaccines to optimal sites in the body. Specifically, effective methods to deliver vaccines into outer skin and mucosal layers--sites with immunological, physical and practical advantages that cannot be targeted via traditional delivery methods--are lacking. This chapter investigates the challenge for physical delivery approaches that are primarily needle-free. We examine the skin's structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Effective cross-talk between innate and adaptive immune responses generates more robust, longer-lasting immune protection [20,21]. We and other investigators have previously reported that skin immunization with metal or dissolving microneedle patches (MNPs) carrying various vaccines (influenza, inactivated poliovirus (IPV), measles, tetanus, HPV, rotavirus, BCG, malaria and RSV) confers immune responses at least non-inferior to conventional immunization as shown by lethal challenge studies, longevity of immune responses and breadth of immunity in a number of small-animal models [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 97%
“…Effective cross-talk between innate and adaptive immune responses generates more robust, longer-lasting immune protection [20,21]. We and other investigators have previously reported that skin immunization with metal or dissolving microneedle patches (MNPs) carrying various vaccines (influenza, inactivated poliovirus (IPV), measles, tetanus, HPV, rotavirus, BCG, malaria and RSV) confers immune responses at least non-inferior to conventional immunization as shown by lethal challenge studies, longevity of immune responses and breadth of immunity in a number of small-animal models [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, jet injectors have also been applied in gene and vaccine delivery [10,11]; however, occasional pain and bruising limit their widespread use [12]. For skin rejuvenation, jet injection uses a precise technology to accelerate and laterally disperse skin-enhancing hyaluronic acid (HA) particles via microtrauma using a pneumatic needle-free mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we test the hypothesis that improved delivery methods can augment the efficacy of vaccines by delivering a test-case protein subunit vaccine, ovalbumin (OVA), to the skin's abundant immune cell population using an ultra-high density (>21,000 microprojections/cm 2 ) microprojection array, the Nanopatch (NP), and measure resultant CD8 + T cell responses. Our rationale for this study comes from a growing body of science showing that vaccine immunogenicity can be improved by targeted delivery to the skin ( [25][26][27][28][29][30][31][32]; among others). Specifically, improved immunogenicity (antibody, CD8 + T cell responses, or both) has been generated by targeting virus-based vaccines (live attenuated) to the skin's immune system when compared to standard intramuscular injection [33,34].…”
Section: Introductionmentioning
confidence: 99%